A frequency multiplier using three ambipolar graphene transistors. (December 2017) - Kabir, Hussain Mohammed Dipu; Salahuddin, S.M.
Abstract: In this paper, a frequency doubler circuit is designed using three ambipolar graphene transistors. Transistors are connected in series, across the voltage source ( V DD ) and the ground ( V SS ). Gates of transistors are shorted; a small AC signal is applied to the gate with a DC bias voltage. The output voltage signal is measured across the source and drain of the middle transistor. As the DC bias point is operated at the minimum-current voltage ( V G_MIN ) of the middle transistor, single swing in the input causes double swing at the output. Furthermore, gates of three transistors can be shared as a common gate without using any connecting wire. Prior to the AC analysis, a DC sweep is performed to visualize the voltage change in each node. The required property of the ambipolar material for the implementation of the proposed circuit is also investigated.